(untitled) (Agricultural Engineering, 2021)
As a result of energy assessment of a pneumatic sieve separator for agricultural crops it was determined that the specific energy consumption of the experimental pneumatic sieve separator was 0.18 kW·year·t−1. It is lower than in case of its domestic and foreign equivalents. For instance, the specific energy consumption of the separator of preliminary grain purification called SPO-50 (Ukraine) is 0.31 kW·year·t−1, and that of the machine of preliminary grain purification called MPO-50 (Russia) is 0.38 kW·year·t−1. Specific energy consumption of a pneumatic sieve separator is 1.72-2.11 times lower than in case of its domestic and foreign counterparts.